2019
DOI: 10.1080/09638288.2019.1641850
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effects of cardiac rehabilitation interventions on cognitive impairment following stroke

Abstract: Purpose:The cardiac rehabilitation model has potential as an approach to providing rehabilitation following stroke. This review aims to identify evidence for the participation of stroke patients in cardiac/cardiovascular rehabilitation programmes internationally, whether or not such programmes offer a cognitive intervention as part of treatment, and the impact of rehabilitation on post-stroke cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The interview topic guide (Appendix 1) was informed by systematic review of the literature completed by the same authors (5,6), in addition to consultation with members of the research team who possess clinical and research expertise in relation to stroke and cognitive rehabilitation.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The interview topic guide (Appendix 1) was informed by systematic review of the literature completed by the same authors (5,6), in addition to consultation with members of the research team who possess clinical and research expertise in relation to stroke and cognitive rehabilitation.…”
Section: Data Collectionmentioning
confidence: 99%
“…Despite the high prevalence of post-stroke cognitive impairment (2,3), cognitive rehabilitation has received considerably less research attention than rehabilitation of post-stroke physical impairment (5,6). Although a recent systematic review reported some promising data in support of cognitive interventions (7), the efficacy of cognitive rehabilitation requires further investigation (5,6).…”
Section: We Don't Really Know What Work…if We Had a Very Clear Pathwa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ihle-Hansen et al’s [ 60 ] 18-month RCT examined the effects of individualized regular coaching and exercise on post-stroke cognition. The Trail Making Test A and B and MMSE were used to assess cognition, with data collected three and 21 months after stroke.…”
Section: What Interventions Exist For Post-stroke Rehabilitation mentioning
confidence: 99%